A Comparative Study Between E-Cigarette Vapor and Cigarette Smoke Exposure on the Lungs of Mice (Mus musculus) - Putri, Mirtanti Kiswandi; Hestianah, Eka Pramyrtha; Kuncorojakti, Suryo; Widiyatno, Thomas Valentinus; Sukmanadi, Mohammad; Santoso, Kuncoro Puguh; Plumeriastuti, Hani; Hidayatik, Nanik; Khairullah, Aswin Rafif (Universitas Airlangga, 2025)
Background: Cigarettes are tobacco products processed with or without additives and are known to contain addictive substances that pose serious health risks to individuals and the public. Inhaled cigarette smoke directly stimulates the activation of macrophage cells in the respiratory tract. Among the affected cells, type II alveolar cells which produce pulmonary surfactant to reduce alveolar surface tension are particularly vulnerable to smoke-induced damage. Purpose: This study aimed to compare the effects of conventional cigarette smoke and e-cigarette vapor exposure on the number of alveolar macrophages and type II alveolar cells in male mice (Mus musculus). Method: A total of 28 male mice were randomly divided into seven groups. The control group (C) was exposed to ambient air only. Groups A1, A2, and A3 were exposed to 1, 2, and 3 conventional cigarettes per day, respectively, while groups B1, B2, and B3 were exposed to 0.7 mL, 1.3 mL, and 2 mL of e-liquid vapor per day, respectively. All exposures were conducted for 36 consecutive days. Results: A significant difference (p<0.05) was observed in the number of alveolar macrophages among groups C, A1, A2 , A3 , B2 , and B3 , whereas no significant difference was found between A1 and B1. The number of type II alveolar cells significantly differed (p < 0.05) across all groups: C, A1, A2, A3, B1, B2, and B3. Conclusion: Both conventional cigarette smoke and e-cigarette vapor increase alveolar macrophage counts and reduce type II alveolar cell numbers compared to controls. Although both exposures pose health risks, e-cigarette vapor appears to cause milder pulmonary effects than conventional cigarette smoke.